The Overlooked Impact of the Round Table Conference: Indonesian Citizenship among the Javanese-Surinamese Community (1949–1975) - Yogaswara Fajar Buwana; Zulkifli Randa (Program Studi Pendidikan Sejarah FKIP Universitas Mulawarman, 2026)
This article examines an overlooked consequence of the Round Table Conference: the adoption and later decline of Indonesian citizenship among the Javanese-Surinamese community from 1949 to 1975. In the early post-sovereignty years, many Javanese-Surinamese chose Indonesian nationality because they imagined Indonesia as their ancestral homeland and expected attention from the new state. Using the historical method of topic selection, heuristics, source criticism, interpretation, and historiography, the study draws on newspapers, sociological works, and related historical literature. The findings show that Indonesia did not ignore the community, as seen in the establishment of its representation in Paramaribo in 1951. However, the Javanese-Surinamese were never a major priority in Indonesia’s early postcolonial agenda. As Indonesian domestic and foreign priorities shifted and Surinamese integration deepened, enthusiasm for Indonesian citizenship steadily weakened.